Chikungunya virus entry and infectivity is primarily facilitated through cell line dependent attachment factors in mammalian and mosquito cells - Reyes Ballista, Judith Mary; Miazgowicz, Kerri L.; Acciani, Marissa D.; Jimenez, Ariana R.; Belloli, Ryan S.; Havranek, Katherine E.; Brindley, Melinda A. (Frontiers in Cell and Developmental Biology, 2023)
Chikungunya virus (CHIKV) is the causative agent of the human disease chikungunya fever, characterized by debilitating acute and chronic arthralgia. No licensed vaccines or antivirals are currently available for CHIKV. Therefore, the prevention of attachment of viral particles to host cells is a potential intervention strategy. As an arbovirus, CHIKV infects a wide variety of cells in both its mammalian and mosquito host. This broad cell tropism might stem from CHIKV’s ability to bind to a variety of entry factors in the host cell including phosphatidylserine receptors (PSRs), glycosaminoglycans (GAGs), and the proteinaceous receptor Mxra8, among others. In this study, we aimed to determine the relevance of each attachment factor during CHIKV entry into a panel of mammalian and mosquito cells. Our data suggest that the importance of particular binding factors during CHIKV infection is highly cell-type dependent. Entry into mammalian Vero cells was mediated through attachment to PSRs, mainly T-cell immunoglobulin mucin domain-1 (TIM-1). Conversely, entry into HAP1 and NIH3T3 was mediated by GAGs and Mxra8, respectively. Entry into mosquito cells was independent of PSRs, GAGs, and Mxra8. Although entry into mosquito cells remains unclear, our data denotes the importance of careful evaluation of reagents used to identify receptor use in invertebrate cells. While PSRs, GAGs, and Mxra8 all enhance entry in a cell type dependent manner, none of these factors are necessary for CHIKV entry, suggesting additional host factors are involved.